The Effect of Organizational Commitment, Motivation and Employee Retention on Employee Performance with Performance Discipline as an Intervening Variable at PT Pelindo Regional I - Ricky Ganda; Kholilul Kholik; M. Toyib Daulay (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the influence of organizational commitment, motivation, and employee retention on employee performance with work discipline as an intervening variable at PT Pelindo Regional I. This study uses a quantitative approach with a survey method, where the population is all 98 permanent employees and sampling is carried out using saturated sampling techniques. Data collection was carried out through a questionnaire with a Likert scale, while data analysis used Partial Least Square-Structural Equation Modeling (PLS-SEM) through SmartPLS. Testing of the outer model includes convergent validity, discriminant validity, and reliability tests, which show that all indicators are valid and reliable after the elimination of one indicator. The inner testing of the model includes R-Square, Q-Square, and Goodness of Fit analysis. The R-Square value shows that Work Discipline is explained by an exogenous variable of 43.1%, while Employee Performance is explained by 49.2%, and a GoF value of 0.558 indicates that the model has a strong level of compatibility. The results of the study show that work discipline has a positive and significant effect on employee performance, which means that the higher the discipline, the better the performance. Organizational commitment has a positive and significant effect on work discipline, but does not have a significant effect directly on employee performance, indicating the need for intermediate variables. Work motivation has been shown to have a positive and significant effect on both work discipline and employee performance, showing that motivated employees will be more disciplined and perform better. Employee retention shows the strongest positive and significant influence on work discipline and also has a significant effect on employee performance, indicating the importance of retaining quality employees. The results of the mediation test proved that work discipline mediated the influence of organizational commitment, work motivation, and employee retention on employee performance significantly, with the strongest mediating effect on employee retention. This study concludes that work discipline is a key variable that mediates the relationship between organizational commitment, motivation, and retention and employee performance at PT Pelindo Regional I.